Cooperation objective evaluation in aviation: validation and comparison of two novel approaches in simulated environment - Capotorto, Rossella; Ronca, Vincenzo; Sciaraffa, Nicolina; Borghini, Gianluca; Di Flumeri, Gianluca; Mezzadri, Lorenzo; Vozzi, Alessia; Giorgi, Andrea; Germano, Daniele; Babiloni, Fabio; Aricò, Pietro (Frontiers in Neuroinformatics, 2024)
In operational environments, human interaction and cooperation between individuals are critical to efficiency and safety. These states are influenced by individuals’ cognitive and emotional states. Human Factor research aims to objectively quantify these states to prevent human error and maintain constant performances, particularly in high-risk settings like aviation, where human error and performances account for a significant portion of accidents. Thus, this study aimed to evaluate and validate two novel methods for assessing the degree of cooperation among professional pilots engaged in real-flight simulation tasks. Additionally, the study aimed to assess the ability of the proposed metrics to differentiate between the expertise levels of operating crews based on their levels of cooperation. Eight crews were involved in the experiments, consisting of four crews of Unexperienced pilots and four crews of Experienced pilots. An expert trainer, simulating air traffic management communication on one side and acting as a subject matter expert on the other, provided external evaluations of the pilots' mental states during the simulation. The two novel approaches introduced in this study were formulated based on Circular Correlation and Mutual Information techniques. The findings demonstrated the possibility of quantifying cooperation levels among pilots during realistic flight simulations. Additionally, cooperation levels were found to be significantly higher (p < 0.05) among Experienced pilots compared to Unexperienced ones. Furthermore, these preliminary results exhibited significant correlations (p < 0.05) with subjective and behavioral measures collected every 30 seconds during the task, confirming their reliability.